Espírito Santo, um estado "satélite" na primeira república : de Moniz Freire a Jerônimo Monteiro (1892-1912) - Sueth, José Candido Rifan (2004)
This study about regional history gives support to understand hegemony of some Brazilian states and exclusion of Espirito Santo, within the First Republic period, a very important phase of political Brazilian history. Genesis of Capixaba heteronomy is analysed in the light of an original interpretation of North American federalism in Brazil, which has played an important part in so called governors policy, as well as in hegemony of some Brazilian states upon federation unities considered secondaries. The chronological time line covers Espírito Santo’s state governments from 1892 to 1912, reaching specially two state governors, José de Carvalho Moniz Freire and Jeronimo de Souza Monteiro that, in spite of differentiate political guide-lines, kept the “satellite” character of Espirito Santo state before Federation. This analysis of documents, as official Messages and Addresses, is based on weberian conception about power and, in spite of not having the goal of using History as “teacher of life”, maybe offers some fundament to notices about Espirito Santo within the 21st century, giving therefore a contribution to a new political history which now characterizes some areas of historiography.